India’s Youth Entrepreneurship Ecosystem: A Comparative Study of India and Other Developing Nations - Dr.Anusuah.R (South Eastern European Journal of Public Health, 2025)
India's entrepreneurial voyage has been centuries long, taking a dramatic turn from the early 18th century to the digital era with globalization and economic liberalization contributing immensely. The emergence of IT centres in the form of Bangalore and Pune and cutting-edge technologies like AI, machine learning, blockchain, and IoT have revolutionized old industries and created opportunities for innovative ventures. This study takes lessons from best success stories worldwide, including Bangladesh's Grameen Bank, Kenya's Ajira Digital Program, Peru's agro-tech projects, and Africa's Anzisha Prize, to present practical recommendations for fortifying India's rural entrepreneurship ecosystem. There are also challenges from the Indian education system that focuses on jobs over entrepreneurial skills, creating a mismatch in skills. Access to funds is another major issue, with rural youth depending mainly on family savings and informal loans. Low awareness of government programs and bureaucratic hurdles are factors that increase these problems. Still, grassroots innovations give hope, such as Kalpana Saroj, who broke caste barriers to revive Kamani Tubes, and Mansukhbhai Prajapati, whose Mitticool environment-friendly clay products transformed traditional pottery. So too, Chetna Sinha's Mann Deshi Mahila Bank gives financial empowerment and business training to rural women. Peru's agro-tech initiatives illustrate blending traditional farming practices with new technology for sustainable farming. Africa's Anzisha Prize promotes young entrepreneurs through recognition and funding. A comparative study indicates similarities and differences. India's Self-Help Group (SHG) model and Skill India programs are consistent with international practice but are challenged by constrained coverage in tribal and off-grid areas. Kenya's emphasis on technology-based youth opportunities and Bangladesh's stress on microfinance hold lessons for India. The research suggests policy enhancements for streamlining access to finance and improving skill building, especially in rural India. Highlighting cost-effective, localized digital solutions and developing public-private collaborations can establish incubation hubs and mentorship schemes. Cross-country partnerships for implementing tested models and launching cultural awareness drives can tackle socio-cultural challenges. With these initiatives, rural youth will be able to harness regional assets, native intelligence, and local aspirations to fuel innovation, economic growth, and social equity. Aligning efforts with global best practices, India will be able to enable its rural entrepreneurs to make a considerable contribution to the nation's vision for Vikshit Bharat 2047.